Analysis of Political Criminalization in Indonesia - Vicki Dwi Purnomo; Hasrul Buamona; wantara (Formosa Journal of Applied Sciences, 2023)
Analysis Political punishment in the form of revocation of rights politics for those convicted of corruption. Method Which used in study This is method study normative law. Judging from its nature, this research is descriptive. Source data in this research is material law primary, material law secondary And material law tertiary. Method withdrawal conclusion in This study uses the deductive method, namely drawing general things to characteristic Which special. From results study This writer observe that happening practice corruption in Indonesia due to weak sentencing for public officials who corruption. Because of that, additional punishment for revocation of rights is imposed Politics basically aims to frighten and provide a deterrent effect to perpetrator corruption, so that official public Which before intend do corruption to be afraid to do it.